Seasonal changes in water-soluble brown carbon (BrC) at Nanling background station in South China - Zhang, Bolong; Tang, Jiao; Geng, Xiaofei; Mo, Yangzhi; Zhao, Shizhen; Zhong, Guangcai; Li, Jun; Zhang, Gan (Frontiers in Environmental Science, 2024)
Brown carbon (BrC) is an important light-absorbing component of organic carbon (OC), causing large uncertainty in aerosol radiative forcing evaluation. Knowledge of BrC in an atmospheric background station is beneficial to understand its role in a changing climate. This study aims at characterizing water-soluble BrC (WS-BrC) in fine particles at Nanling background station in South China. A total of seventy-two PM2.5 samples throughout a year were used. The low levels of PM2.5, OC, and elemental carbon (EC) conferred a background site. The optical properties of WS-BrC were characterized using excitation-emission matrix (EEM) fluorescence spectroscopy. The WS-BrC made a significant contribution (365 nm, 18 ± 10 %) to total carbonaceous aerosol absorption. The mass absorption efficiency (MAE) of WS-BrC is 0.81 ± 0.34 m2 gC–1, and varies among seasons due to the different sources or atmospheric processing. Three EEM fluorescent components were identified by parallel factor (PAFAFAC) analysis, including two humic-like substances (HULIS, C1, C2), and one phenolic-like component. The HULIS components accounted for approximately 70% of the total fluorescence intensities. Primary combustion emissions showed enhanced activity during the winter and spring seasons, but there were no significant influences on WS-BrC in spring. Secondary sources contributed significantly to WS-BrC during winter, summer, and autumn (all exceeding 50%), except for spring. Photooxidation is a significant process in the formation of secondary WS-BrC in winter and autumn, but there may be another formation pathway in summer, i.e., the ammonia pathway. This study contributes to our understanding of BrC in the background atmosphere.